Wet‐Spun Bioelectronic Fibers of Imbricated Enzymes and Carbon Nanotubes for Efficient Microelectrodes. Issue 12 (16th September 2015) - Mateo‐Mateo, Cintia; Michardière, Anne‐Sophie; Gounel, Sébastien; Ly, Isabelle; Rouhana, Jad; Poulin, Philippe; Mano, Nicolas
Abstract: The electrical connection of enzymes and microelectrodes is usually achieved through the direct deposition of biomolecules at the electrode surface. Optimization of this interface can be achieved by using conductive nanomaterials such as carbon nanotubes, by adding shuttles of electrons, and/or by tuning the geometry of the electrode. However, immobilized enzymes remain essentially located at the outer surface of the electrode, thereby limiting the current density of the devices. A single‐step, scalable wet‐spinning approach that allows the fabrication of microfibers into which enzymes and carbon nanotubes are imbricated in the core of the fiber is reported in this work. The efficiency of these bioelectronics fibers is tested in the enzymatic reduction of O2 and glucose oxidation. The presented microelectrodes exhibit a significantly enhanced activity compared to surface‐coated microelectrodes, while preserving all of the advantages of microelectrodes in terms of miniaturization and spatiotemporal resolution. Abstract : A special arrangement : A scalable, single‐step, wet‐spinning approach that allows the fabrication of microfibers into which enzymes and carbon nanotubes are imbricated in the core of the fiber is reported. A sevenfold increase in current density and a significantly improved stability can be achieved by using the present protocol compared to a usual surface‐coating method.